Buddhism, Christianity, and psychotherapy: A three-way conversation in the mid-twentieth century. Issue 1 (2nd January 2018) - Harding, Christopher
Abstract: This article explores the scope of 'religion-psy dialogue' in the mid-twentieth century, via a case study from Japan: Kosawa Heisaku, a Buddhist psychoanalyst based in Tokyo. By putting this case study in brief comparative perspective, with the conversation that took place in 1965 between Paul Tillich and Carl Rogers, the article discusses both the promise and the pitfalls of the modern and contemporary world of 'religion-psy dialogue', alongside the means by which specialists in a variety of fields might investigate and hold it to account.